The study of microbial contamination of water and sanitary facilities in the Karaganda regional clinical hospital during different seasons - Akhmetova, S.B.; Belyayev, I.A.; Omarova, A.O.; Amirkhanova, Zh.T. (Fundamental and Experimental Biology, 2022)
In modern conditions, the quality of water supply and the state of water management facilities play a key role in maintaining the health of people and animals, as well as the life quality of the population. In this regard, we set the goal of our research to assess the level of microbial contamination of water and sanitary facilities in the Regional Clinical Hospital of Karaganda district as the central and most powerful medical institution in the region in different seasons of the year. Based on the results of our study, the following conclusions can be drawn: during the research period, seasonal variability of indicators in the studied samples of tap water can be traced. The water of the central water supply is characterized by systematic excesses of both total coliform and thermotolerant coliform bacteria. In the city of Karaganda, there is a great stability in the quality of water supply, regardless of the seasons, despite the excess of standard indicators. It can talk about either the low quality of water treatment, or about quality problems in the water supply network at the sampling points (Re-gional Clinical Hospital of Karaganda). At the same time, it is worth noting the high percentage (almost 98 %) of positive samples in the spring. In winter, there is a lower percentage of positive samples and a sig-nificantly lower microbial quantity. The quality of drinking water decreases in the spring, we believe that the most likely reason for the deterioration in the quality of drinking water is the ingress of melt water and rain-water into the source. Violations of the technological conditions for the operation of water treatment facilities, secondary water pollution in worn-out water distribution networks could also be the cause of unsatisfactory results. In the Regional Clinical Hospital of Karaganda, a higher percentage of positive swabs is noted, which is associated with a higher load on the regional hospital, as well as a better supply of antimicrobial disinfectants, which leads to selective selection of more resistant strains.